Ice-induced vibrations of wind turbines with a jacket support structure - Marsman, Irene (author) (2018)
The offshore wind industry is a relatively new but fast growing field in the global shift towards renergy to reduce carbon emissions. However, more difficulties arise in the design of an offshore wind turbine (OWT) compared to an onshore wind turbine, as the offshore structures are exposed to more environmental influences. One of those is sea ice. As wind farms are being built in areas where floating sea ice exists, such as the Baltic Sea and Bohai Bay, the effect of interaction of ice with an offshore wind turbine needs to be taken into account in the design phase. Several accidents have taken place in the past, where offshore structures such as bridges, lighthouses and oil platforms were exposed to severe ice loading, leading to human discomfort and damage or even failure of the structure. Recent research has shown that ice-induced vibrations (IIV) can develop in wind turbines with a monopile foundation. This research studies IIV in a wind turbine with a jacket foundation, which is used in deeper waters. These IIV can be categorized into three regimes: intermittent crushing (IC), frequency lock-in (FLI) and continuous brittle crushing (CBR), depending on both structural and ice properties. During IC, which occurs for low ice velocities, large forces act on the structure. For higher velocities, the failure of ice ‘locks in’ with one of the structural eigenmodes, leading to the FLI mode, where cyclic loading of the structure sustains. This periodic movement affects the fatigue of the structure. When ice is moving at even higher velocities, the CBR regime begins, in which the ice load does not show a periodicity but fluctuates around a relatively low mean value, resulting in small, random oscillations of the structure around the mean deflection. In this research, the effect of these IIV on offshore wind turbines with a jacket foundation was investigated. To that end, a structural model for a 5MW wind turbine has been implemented and a preliminary study indicated that the second eigenmode is most susceptible to ...